SLAVE SWING THE MALAY TRADITION VILLAGE SUB CHART KENCANA SINEMBAH (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Culture is the result of cultivation and human, culture grows and develops cumulatively, consciously and deliberately . Culture is of great significance for a nation, the nation's culture would appear to be a nation that is quite perfect level of life. Culture in the form of a collection of a few individuals who have the background and characteristics of its own in accordance with the environment in which the individual resides. The purpose of this study was (1) to determine how the Swing tradition Slaves Malay Society. (2) To know the process of implementation of the Slave Swing tradition. (3) to determine the values of what is contained in the Slave Swing tradition. (4) To determine the perception of the younger generation of this slave Swing traditionand (5) How is the effort to preservethe traditio of the Malay Society Slaves Ayun . These results indicate that this slave Swing tradition is a ritual performed for the new baby a few days old and combined with aqiqah ceremony, so the flour offer you an activity shave and baby always initiated this event. Slaves swing is one that is full of Malay tradition and the meaning of religious values (religion) andis a form of ceremony performed when mothers would lull her in a swing with song scontaining advice and prayer.Keywords: Tradition, Ayun Slaves